(untitled) (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Ethnobiological scholarship has provided rich contextual evidence of the myriad ways in which Indigenous Peoples’ long-term connections with their lands are essential for sustaining biodiversity in different local contexts. However, our discipline is still finding ways to promote effectively the scalability of place-based ethnobiological evidence in order to unveil global trends and patterns in more systematic ways. In this talk, I will present how the use of geospatial analysis is gaining momentum as an important tool to characterize, both quantitatively and qualitatively, biodiversity patterns in Indigenous lands at the global scale. I will give an overview of current efforts to map the global extent of Indigenous Peoples’ lands and their biocultural attributes. I will also show how these advances, based on the best available geospatial evidence, are being employed to inform policy debates around the role of Indigenous Peoples in global biodiversity maintenance, and to support Indigenous Peoples’ advocacy in international environmental negotiations. I will conclude by highlighting how the use of such methods can contribute to expand global scientific knowledge of the factors, pathways and mechanisms associated with Indigenous Peoples’ stewardship practices, and bring ethnobiological knowledge into resolutions that can influence global environmental policy agendas.